THE INFLUENCE OF STUDENTS’ LEARNING STYLES ON THE UNDERSTANDING OF READING TEXTS - Qurinta Shinta (Bajang Institute, 2023)
This research aimed to find out the influence of students’ learning styles on their understanding of reading comprehension for students of Communication Science taking the English Course in the 2022/2023 Academic year. This research was a quantitative approach. The sample of this research was 51 students of Communication Science at USM who took the English Course. These samples were taken by using a random sampling technique. The data were collected by using questionnaires and students’ final scores on reading comprehension tests. The data were analyzed by using the regression technique with SPSS version 24.0 for Windows. The research findings show that students’ learning style gave an influence on their reading comprehension which was shown by their final scores.